AKIBAT HUKUM (IMPLIKASI YURIDIS) PERKAWINAN BEDA AGAMA PERSPEKTIF PASAL 2 JO PASAL 21 UNDANG-UNDANG PERKAWINAN NO 1 TAHUN 1974 - Muhammad Nafis; Khoirul Asfiyak; Dwi Ari Kurniawati (Jurnal Hikmatina, 2019)
Indonesia has different: culture such us group and ras, many factors  Indonesia has different culture, the fortos is the geografi situation, because the high factor has many style. After all, even though it must have been really bad for men who were visited by men and women who were living in some place. The problem of married with the other religion is still a polemic,  in the reality of people’s lives the practice of interfaith marriage in Indonesia can’t be avoided, while the implementation of interfaith marriage it self in community is relate very difficult. In the conception of Indonesia law, the  problem of marriage has been regulated nationally, in law number one of concerning marriage, which is officially valid from the date of promulgation, in 2 of January 1974. Then became effective in 1 october 1975 though regulation the government of republic Indonesia No. 9 of 1975 concerning the implementation of number law 1 of 1975 concerning marriage. The purpose of this research how to find the legal impact (juridical implication) of interfaith marriage in the perspective  of article 21 of marriage law no 1 of 1974. This research is a library research that is legal  normative legal research, using several approaches, is the legislative approaches other related approaches to regulation. The research specification in this paper are descriptive analytical in nature, so that later in the expected to be able to know the implementation of inter faith  marriage to compherensive frame of law number I of 1974 concerning marriage. The result of this research that law no 1 of 1974 concerning marriage, there are no stret rules for inter faith marriage in Indonesia.  So that this raises a polemic in understanding and the implementation , even relatively inconsistent this can be show in article 2 paragraph (1), article 8 letter (f) and article 21 paragraph (3) and (4) number one of 1974 years concerning marriage. Keyword : Interfaith Marriage, The validity of marital law, Law No. 1 of 1974.